Effects of topical polydeoxyribonucleotide on radiation-induced oral mucositis. (September 2018) - Podlesko, Anna M.; Ramacciati, Nicola; Panzolini, Serenella; Saldi, Simonetta; Fiorucci, Serenella; Pierini, Daniela; Mancini, Marina; Merolla, Maria S.; Lancellotta, Valentina; Aristei, Cynthia
Highlights: Oral mucositis (OM), the most common toxicity in patients with head and neck cancer. Polideoxyribonucleotide (PDRN) is highly regenerative and anti-inflammatory drug. OM lesions were attenuated to Grade 2 within the first week of PDRN treatment. Pain was relieved about 2–3 days after starting treatment with PDRN spray. All the patients completed Radiotherapy and chemotherapy without any interruptions. Abstract: Introduction: Oral mucositis, the most common adverse effect of radiotherapy (RT) and/or chemotherapy is observed in almost 97% of patients with head and neck cancer. Although several agents like corticosteroids, lidocaine and vitamins are available for its prevention or management, results are often disappointing. Here we report on the effects of a topically applied, highly purified natural deoxyribonucleic acid from sturgeon gonads on three cases of moderate to severe oral mucositis in patients with head and neck cancer. Case Description: Three patients who had undergone RT and/or chemotherapy received an oral spray containing sodium salt-based natural deoxyribonucleic acid (PDRN) for Grade 3 oral mucositis. Treatment continued for one month after the end of RT. No patient reported any allergic reactions. RT and chemotherapy were not interrupted and opioid therapy was not given to any patient. Pain was relieved about 2–3 days after starting treatment and oral mucositis was reduced to G2 within one week. Conclusions: Outcomes in all 3 cases showed topical use of the sodium salt-based PDRN derived from sturgeon gonads was acceptable and safe when used topically for therapeutic and regenerative purposes. Present results are encouraging and suggest a more in-depth study is warranted on its use in a larger patient cohort with RT-induced oral mucositis.